Orthogonally Integrating Programmable Structural Color and Photo‐Rewritable Fluorescence in Hydrazone Photoswitch‐bonded Cholesteric Liquid Crystalline Network. (15th November 2022) - Lan, Ruochen; Bao, Jinying; Li, Zhaozhong; Wang, Zizheng; Song, Chenjie; Shen, Chen; Huang, Rui; Sun, Jian; Wang, Qian; Zhang, Lanying; Yang, Huai
Abstract: Design and fabrication of advanced security label showing superior performance in data encryption has attracted tremendous scientific interests. Especially, multifunctional optical labels capable of storing distinct information in different modes are highly demanded. Here, a fluorescent cholesteric liquid crystalline network (CLCN) film with programmable visible patterns and photo‐rewritable fluorescent patterns was designed and prepared. The visible patterns were fixed by helical network and the colors of visible patterns were tunable by changing relative humidity (RH). The fluorescent patterns originated from dynamic isomerization of fluorescent hydrazones, exhibiting highly thermal stability and switching‐ability controlled by light. The orthogonal construction of visible and fluorescent pattern enabled the novel CLCN to encrypt distinct information in reflective mode and in emissive mode, indicating its potential in anti‐counterfeiting and information encryptions. Abstract : This work realized construction of distinct visible and fluorescent patterns in a single freestanding photonic film by integrating water‐swellable helical polymer matrix and fluorescence switchable molecular switch. The orthogonally dual responsiveness of the novel optical materials enabled fabrication of anti‐counterfeiting and information encryption devices with superior safety and capacity.